Social-Fairness Perception in Natural Disaster, Learn from Lombok: A Phenomenological Report - Filipus Michael Yofrido; Lila Tri Harjana (Faculty of Medicine-Universitas Airlangga, 2019)
Introduction: Disasters occur in all areas of the world and cause harm to populations, property, infrastructure, economies, and the environment.1Harm to populations includes death, injury, disease, malnutrition, and psychological stress.1Social-friction often isn't recognized during disaster response and recovery. Objective: This report explored the existence of social-friction in disaster situation which able to make recovery more complex. Method: This was qualitative study with phenomenology report approach. The data collection was done by indepth interviewing five inhabitants when doing emergency disaster response two weeks after massive earthquake in North Lombok. Result and discussion: Two out of five inhabitants were Lombok native-people, the rest were immigrant. An inhabitant reported their feeling treated unfair by aid agencies because they received less aid than others. In another chance, when distributing clean-water, we were intercepted, they argue that they got more lack of water than another group who live far distally. Both claimed treated unfair making a dispute friction.Ethnic or social origin, language, religion, gender, age, physical or mental disability, and sexual orientation are just some of the deep-rooted causes of social-friction that can have such a devastating impact on their lives.Social-friction in everyday life rarely endangers lives, but in an emergency situation, it can be life-threatening. It affects not only people's ability to survive the crisis, also their capacity to recover and regain their livelihoods. Conclusion: Risk reduction and preparedness are just as important a part of the process as any aspect of a disaster.Dialogue is fundamental in good programme design, monitoring and evaluation, and systematic efforts to listen to all groups affected by disaster can help pre-empt and remedy unfair-perception.Perhaps,most importantly, understanding and respecting the complex cultural context in which aid agencies are working and using the strategies and mechanismsto detectand minimize social-friction, will result great improvement in the effectiveness and equity of perceived support in humanitarian assistance.2